Martingale Morrey-Hardy and Campanato-Hardy Spaces. (20th October 2013) - Nakai, Eiichi; Sadasue, Gaku; Sawano, Yoshihiro
Abstract : We introduce generalized Morrey-Campanato spaces of martingales, which generalize both martingale Lipschitz spaces introduced by Weisz (1990) and martingale Morrey-Campanato spaces introduced in 2012. We also introduce generalized Morrey-Hardy and Campanato-Hardy spaces of martingales and study Burkholder-type equivalence. We give some results on the boundedness of fractional integrals of martingales on these spaces.